Peran Public Relations PT. KCIC dalam Membangun Brand Awarenees Kereta Cepat Whoosh - Maulidina Wamareta Putri; Winda Dwi Astuti Zebua (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
PT. The Indonesian China Fast Train is one of the companies operating in the field of public transportation services under the auspices of the government which was inaugurated directly by the President of Indonesia, namely Mr. Jokowi, who collaborates directly with China. This research aims at the Role of Public Relations Expert Prescriber PT. KCIC in building Brand Awareness for the Fast Train whoosh, the Role of Public Relations PT. KCIC as Communication Facilitator in building Brand Awareness regarding the Whoosh Fast Train, Role of Public Relations PT. KCIC in Communication Technician to build Brand Awareness of the Whoosh Fast Train, the Role of Public Relations as a Problem Solving Facilitator in handling the issue of the Whoosh Fast Train "Whoosh" Fast Train. The approach used in this research is qualitative with descriptive methods using data collection techniques, documentation and direct interviews with informants. Using triangulation techniques and data analysis using Dozier & Broom's Public Relations Role theory in Ruslan (2020). For the information obtained, 2 informants were interviewed, consisting of key informants, supporting informants and 1 triangulation. The results of this research found that PT Kereta Cepat Indonesia China's public relations will continue to provide updated information using social media and the available the public continues to remember the existence of the Whoosh Fast Train.